Modeling of the Aerial Capacity through a Leontief Production Function: The Case of Tunisian Airports - Besma, Harizi; Riadh, Harizi; Rafaa, M'raïhi (Journal of Reviews on Global Economics, 2017)
Our objective is to model the airport capacity through a Leontief production function, which is based on the complementarity of the factors defining airport capacity. Results of our simulation for all Tunisian airports show that we can determine, especially, foreseeable future of the congestion, traffic processed by infrastructure, availability of infrastructures, the factors that block the circulation on the ground, and time measurements: delays, waiting time, and runway occupancy time. According to their capabilities (reduced, declared, optimal), three airports are identified. However, it is possible to avoid the extra costs experienced by the terminals and to optimize airports' capacity by making a reallocation of human resources and opting for a better exploitation of the existing infrastructures.